2017
DOI: 10.18388/abp.2016_1437
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on β-casein gene Met183QVal183 polymorphism in Romanian indigenous Zackel sheep breeds

Abstract: Genetic polymorphisms of the milk protein genes are important because of their effects on quantitative traits and technological properties of milk manufacturing. In the present study we identified the polymorphism of the beta-casein gene in two local sheep breeds (Racka n=98 and Turcana n=111) in Romania. The most studied variants at the ovine beta-casein (CSN2) locus are: A and G variants. Genomic DNA was extracted from hair follicles and beta-casein genotypes were determined by the rapid TaqMan (Applied Bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Chessa et al [10] reported a missense mutation (rs416941267) in the CSN2 that changed C to A protein alleles inCSN2. The molecular characterization and the association between CSN2 polymorphisms with milk performance were studied in sheep [12,15,16]. This is the first study designed to screen the commercial Awassi sheep CSN1S1 and CSN2 genes loci and investigate their single and combined effects on CSN2 genes and their association with milk production and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Chessa et al [10] reported a missense mutation (rs416941267) in the CSN2 that changed C to A protein alleles inCSN2. The molecular characterization and the association between CSN2 polymorphisms with milk performance were studied in sheep [12,15,16]. This is the first study designed to screen the commercial Awassi sheep CSN1S1 and CSN2 genes loci and investigate their single and combined effects on CSN2 genes and their association with milk production and composition.…”
Section: Introductionmentioning
confidence: 99%